The Effectiveness of Polysilicone Coated Chitosan-Nanosilver as a Disinfectant in Drinking Water Treatment Processes - Nisah, Firda Ainun; Winarsih, Neneng; Nuraini, Umi; Mubarok, Yoga Ulya; Ramadhan, Muhammad Ragil; Febrian, Faris Diaztu (Magister Program of Material Science, Graduate School of Universitas Sriwijaya, 2025)
The need for clean and safe drinking water is increasing, so innovative disinfection methods are needed. This study evaluates the effectiveness of Polysilicone coated with Chitosan-Nanosilver (PCAg) as a disinfectant for drinking water treatment. The synthesis process involves the reduction of silver nitrate (AgNO3) with sodium citrate, which is then combined with chitosan in an acetic acid solution to produce a stable mixture of nanoparticles. This solution was then impregnated into polysilicone foam to create a functional filter media. The experimental results showed that the PCAg were able to effectively remove bacterial contaminants, including Escherichia coli and Total Coliform, from the distilled drinking water samples from 4 CFU/100mL to 0 CFU/100 mL, as per the quality standard of the Ministry of Health of the Republic of Indonesia number 2 of 2023. Analysis of the SEM-EDX characterization method showed an evenly distributed Chitosan-Nanosilver coating on the polysilicone surface, evidenced by the detection of 1.31% Nanosilver and an increase in carbon percentage from 40.16% to 44.98%. In addition, analysis of the FTIR characterization method showed the presence of peaks indicating alkane vibrations, aromatic rings, ester groups, and amine groups typical of chitosan. This indicates that chitosan has been coated on polysilicone. This study concludes that the coating process enables optimal interaction between chitosan, silver nanoparticles, and polysilicone, thus enhancing the antibacterial properties of the material. Thus having a significant ability to eliminate bacteria.